Erv1 associated mitochondrial import-export pathway and the cytosolic iron-sulfur protein assembly machinery in Trypanosoma brucei - Basu, Somsuvro (Jihočeská univerzita, 2014)
This thesis highlights a divergent mitochondrial intermembrane assembly pathway in the parasitic protist Trypanosoma brucei. A comparative genomic study reveals the connection of Erv1 with the cytosolic iron-sulfur protein assembly (CIA) pathway in trypanosomatids. Further, the CIA machinery of T. brucei has been described using RNAi interference and other biochemical and complementation assays. Finally, part of the divergent CIA machinery has been identified in the human intestinal pathogen Giardia intestinalis by means of complementation assays in T. brucei.
Erv1 associated mitochondrial import-export pathway and the cytosolic iron-sulfur protein assembly machinery in Trypanosoma brucei
Keywords: CIA pathway; Fe/S cluster; Trypanosoma brucei; MIA pathway; RNAi; CIA pathway; Fe/S cluster; Trypanosoma brucei; MIA pathway; RNAi